KOMUNITAS SENI CUKIL OMAH LARAS - Faisal, Yusuf (Jurnal Pendidikan Seni Rupa Undiksha, 2021)
AbstrakTujuan dari penelitian ini adalah untuk mendeskripsikan (1) proses berkarya komunitas seni cukil Omah Laras, (2) jenis karya komunitas seni cukil Omah Laras, dan (3) tema karya komunitas seni cukil Omah Laras. Subjek dan Objek dalam penelitian ini adalah karya-karya seni grafis dari komunitas Omah Laras. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan menggunakan metode deskriptif. Pengumpulan data ini menggunakan teknik observasi, wawancara, dokumentasi, dan kepustakaan. Dari pembahasan serta proses penelitian maka dapat disimpulkan sebagai berikut: (1) proses berkarya komunitas Omah Laras dapat dibagi beberapa tahapan, mulai dari tahap persiapan, inkubasi, iluminasi dan verifikasi. (2) jenis karya yang dihasilkan komunitas Omah Laras adalah karya seni grafis yang menggunakan teknik cukil kayu dan teknik stensil. (3) tema karya komunitas Omah Laras tidak jauh dari topik atau isu-isu sekitar, antara lain tema tokoh musik, tema hiburan / parodi, tema sosial dan tema yang mengangkat tokoh para pahlawan yang membela rakyat.Kata kunci : Seni Cukil, Komunitas Omah LarasÂ AbstractÂ The purpose of this research is to describe (1) the work process of the woodcut of Omah Laras community, (2) the types of work of the woodcut community in the art woodcut of Omah Laras community, and (3) the theme of the work of the woodcut of Omah Laras community. Subjects and objects in this study were graphic art works from the Omah Laras community. The method used in this research is a qualitative method using descriptive methods. This data collection uses observation, interview, documentation, and literature techniques. From the discussion and research process it can be concluded as follows: (1) the work process of the Omah Laras community can be divided into several stages, starting from the preparation, incubation, illumination and verification stages. (2) the type of work produced by the Omah Laras community is graphic art that uses woodcut techniques and stencil techniques. (3) the theme of the work of the Omah Laras community is not far from the topic or surrounding issues, including music themes, entertainment / parody themes, social themes and themes that raise heroes who defend the people.Keywords: Woodcut, Omah Laras Community